Konsep Hukum Ekonomi Syariah Serta Implementasinya Di Negara Muslim Dan Non-Muslim - Amany, Amany; Mukhlas, Oyo Sunaryo; Rusyana, Ayi Yunus; Sulthonuddin, Bung Hijaj (Jurnal Hukum Ekonomi Syariah, 2024)
Islamic economics is an economic system that utilizes Islamic law as its foundation. Although rooted in Islamic law, this economic system remains open to participation from non-Muslim communities. The primary focus of Islamic economics is on collective prosperity rather than merely seeking profit. As a result, many countries that are not predominantly Muslim, or even those with liberal governments, implement the principles of Islamic economics across various aspects. One of the main implementations of Islamic economics is through financial institutions such as Islamic banking, known in Indonesia as Sharia Banking. This research aims to analyze the concept of Islamic economic law and its implementation in both Muslim and non-Muslim countries. By utilizing a literature study method, this research examines the application of Islamic economic law in various countries and the role of Islamic financial institutions. The findings indicate that the implementation of Islamic economic law in Muslim countries is more integrated compared to non-Muslim countries, which have only adopted it partially to meet the demands of the Islamic market.  Keywords: Islamic Economic Law, Implementation, Islamic Banking, Muslim Countries, Non-Muslim Countries